Occurrence of autoantibodies for gastrointestinal autoimmune diseases in children with common variable immune deficiency and selected IgA deficiency - Pituch-Noworolska, Anna; Błaut-Szlósarczyk, Anita; Zwonarz, Katarzyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: Selected IgA deficiency (IgAD) and common variable immune deficiency (CVID) are humoral immunity deficiencies frequent in children. In both these types of immunodeficiency, autoimmune diseases are present in 20–30% of patients, but the disease profiles are different between adults and children. Autoimmune diseases of the gastrointestinal tract (IBD) and celiac disease are typical for children with IgAD and CVID. Diagnosis is based on clinical symptoms, histology of jejunum and antibodies often preceding the onset of disease. However, the diagnosis of IBD and celiac disease is difficult in immune deficiency patients due to weaker or absent production of antibodies, and different jejunum histology, particular in CVID patients. Aim: Detection of antibodies for autoimmune diseases in children with diagnosis of CVID and IgAD. Material and methods: The study included 43 children with CVID and 63 children with IgAD diagnosis. Antibodies typical for celiac disease (for endomysium, tissue transglutaminase and gliadin) were tested in IgA class (CVID patients), IgG class (IgAD, CVID patients) and found in 16 patients (3 – CVID, 13 – IgAD). Results: Antibodies for IBD (for Saccharomyces cerevisiae antigen – ASCA, goblet cells – Gab, neutrophil’s cytoplasm – ANCA, pancreatic cells – Pab) were noted in 17 patients (7 – CVID, 10 – IgAD). Celiac disease was diagnosed in two children with mild and unspecific clinical symptoms followed by introduction of a gluten-free diet. The remaining children with present antibodies but without clinical symptoms involving the gastrointestinal tract are under careful clinical observation with antibody assay every 6 months. Conclusions : The antibodies are produced despite impaired humoral immunity but the level might be low so the lower limit of positive results is postulated.